PENGARUH KOMBINASI EKSTRAK ETANOL DAUN SIRSAK DAN GEMFIBROZIL TERHADAP KADAR TRIGLISERIDA DAN HDL TIKUS YANG DIINDUKSI PAKAN TINGGI LEMAK - Ririn Lispita Wulandari; Sri Susilowati; Sucyati Amelya (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Soursop leaves ethanol extract (SLEE) has been shown to lower blood levels of total cholesterol. However, it not yet investigated the effects on triglyceride and HDL levels. There is also no research on combining related soursop leaves with gemfibrozil. The purpose of this study is to compare the efficacy of combination therapy SLEE and gemfibrozil to SLEE or gemfibrozil single treatment on decreasing triglyceride levels and increase HDL level in rats induced by high-fat feeding. Thirty male Wistar rats were divided into six groups (normal control, hyperlipidemia control, single gemfibrozil, single SLEE, 1st combination, and 2nd combination groups). Each group treated a high-fat feed two times a day for 14 days, except for the normal control. The test material was treated one time a day for five days. Measurement levels of triglycerides and HDL used GPO-PAP reagent and Direct Enzymatic Colorimetric Test. The data was analyzed by One-Way ANOVA test followed by Tukey's test. The results showed that SLEE can decrease triglyceride’s level and increase HDL levels of male Wistar rats. The combination of SLEE and gemfibrozil also can decrease triglyceride’s level and increase HDL level. However, there are no significances different between the efficacy of combination SLEE and gemfibrozil than SLEE or gemfibrozil single treatment in decreasing triglyceride's level and increase HDL levels of male Wistar rats. Keywords: Hyperlipidemia, triglyceride, HDL, Soursop leaves ethanol extract, gemfibrozil.